Application analysis of Six Sigma DMAIC model in new nurse training and effects of nutritional diet nursing on postoperative nutritional status in the elderly patients with fracture - Xiong, Fangfang; Tang, Jiao; Han, Han; Wang, Xue; Cao, Jing; Wang, Xianglei; Zhao, Qinghua (Frontiers in Medicine, 2025)
BackgroundIn the current medical system, the insufficient efficiency of the standardized training for new nurses is a major issue. At the same time, elderly patients with fractures are prone to nutritional deficiencies after surgery, which seriously affects their rehabilitation process and treatment outcomes.ObjectivesThis study evaluated the application of the Six Sigma DMAIC model in the training of new nurses, as well as the impact of nutritional diet nursing on the postoperative nutritional status in the elderly patients with fractures.MethodsThis was a prospective intervention study. From September 2021 to September 2022, 260 newly recruited female nurses were randomly divided into the study group and the control group using a random number table method. The control group received traditional training management model, while the study group received training using the Six Sigma DMAIC model. In addition, from November 2022 to November 2023, a total of 80 elderly patients with fractures received treatment were divided into two groups: one group received conventional nursing, and the other group received nutritional diet nursing.ResultsTwo years later, the study group outperformed the control group in terms of theoretical and practical assessment scores, critical thinking ability, self-efficacy, and training satisfaction, with significant difference (p < 0.05). Compared to the conventional nursing group, the nutritional diet nursing group had shorter incision drying time, shorter drainage placement time, and shorter healing time, with significant difference (p < 0.01). After nursing, the levels of albumin, prealbumin, total protein, and immunoglobulins were higher in the intervention group compared to the routine nursing group, with significant difference (p < 0.05). Compared to the routine nursing group, the intervention group also had a lower incidence of complications, with significant difference (p < 0.05 and p = 0.03).ConclusionThe Six Sigma DMAIC model effectively improves the quality of nurse training, while nutritional diet nursing enhances postoperative healing, nutritional status, and immune function in elderly fracture patients.